Genetic assessment wait time indicators in the High Risk Ontario Breast Screening Program. Issue 2 (25th January 2018) - Eisen, Andrea; Blackmore, Kristina M.; Meschino, Wendy S.; Muradali, Derek; Carroll, June C.; Majpruz, Vicky; Warner, Ellen; Rabeneck, Linda; Chiarelli, Anna M.
Abstract: Background: The Ontario Breast Screening Program (OBSP) expanded in July 2011 to screen high‐risk women aged 30–69 with annual MRI and mammography. This study evaluated wait time (WT) indicators along the genetic assessment (GA) pathway for women referred to the High Risk OBSP. Methods: Information was collected for 27, 170 women referred to the High Risk OBSP from July 2011 to June 2015 and followed for GA until June 2016. Median duration (days), interquartile range (IQR) were measured for each WT indicator by program year, age, prior breast cancer, and risk criteria. Results: Among 24, 811 women who completed GA, 16, 367 (66.0%) had genetic counseling only, 8, 444 (34.0%) had counseling and testing and 8, 027 (32.4%) met the high risk criteria. Median WT from physician visit to first screen was longer for women having genetic counseling only compared to those having counseling and testing (244 vs. 197 days). Women having counseling only also experienced the longest WT from physician visit to genetic counseling (88 days; IQR = 10–174), which increased by year from 71 to 100 days ( p  < .0001). Among women having counseling and testing, WT from physician visit to counseling was shortest for mutation carriers (39 days; IQR = 4–100). Median WT from testing to laboratory report issue was 41 days (IQR = 22–70) and 17 days to disclosure of test results (IQR = 7–33). Both WTs decreased with year and were shorter for mutation carriers (33 days, IQR = 19–58; 15 days, IQR = 7–28, respectively). Conclusions: After implementation of the High Risk OBSP, women received timely genetic counseling, in particular those having counseling and testing. Effective triage models for physicians could reduce WT to GA after physician referral. Abstract : This study evaluated wait time (WT) indicators along the genetic assessment (GA) pathway for women referred to the High Risk Ontario Breast Screening Program (OBSP) from July 2011 to June 2015 and followed for GA until June 2016. The wait time from initial physician visit to genetic counseling was longest for women referred for counseling only, whereas among women having counseling and testing, mutation carriers experienced the shortest wait times along each phase of the genetic assessment pathway. Although, most women received timely genetic counseling and, if appropriate, genetic testing and reporting of results, effective triage models for physicians could reduce WT to GA after physician referral.